Hubungan Antara Perawatan Kaki dengan Risiko Ulkus Kaki Diabetes di Rumah Sakit PKU Muhammadiyah Yogyakarta - Arianti Arianti (Universitas Muhammadiyah Yogyakarta, 2015)
Background: Diabetes Melitus (DM) is one of chronic diseases that exist in all countries in the world and keep growing signifi cantly from year to year. There were 366 million people with diabetes mellitus worldwide in 2011, and is expected to increase to 552 million people in 2030. Most of the people with diabetes live in low and middle income countries. Indonesia has 7.3 million people with diabetes in 2011, and is predicted to increase to 11.8 million in 2030. Long term complication from diabetes, both microvascular and macrovascular, can cause insuffi ciently blood supply to hills which can culminate to ulcer infection and will end with an amputation.Goal:The purpose of this research is to know the relationship between foot care and ulcer risk of diabetes foot.Methode: This research method is non experimental- correlational with cross sectional design. In this research, there are 45 respondents.Result:Based on bivariate analysis, it is known that self foot care (p=0.003) and footwear choice and usage (p=0.009 have significant correlation with ulcer risk of diabetic foot. Continued with multivariate analysis, self foot care related to ulcer risk with p0.005 (p=0.01). People with diabetes who get good foot care have chance to prevent diabetes foot ulcer risk 14 times compared with people with diabetes who get poor foot care.Conclusion: The conclusion of this study are highly correlated independently foot care in the prevention of diabetic ulcers. Based on this study are expected for nurses to conduct a study to diabetic foot conditions and provide education about diabetic foot care.Key words: foot care, foot ulcer, diabetes melitus.